2020
DOI: 10.1096/fj.201903100rr
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of dynamin‐related‐protein 1 in dynamics of ER‐lipid droplets in adipose tissue

Abstract: Dynamin‐Related‐Protein 1 (DRP1) critically regulates mitochondrial and peroxisomal fission in multicellular organisms. However, the impact of DRP1 on other organelles, especially its direct influence on ER functions remains largely unclear. Here, we report that DRP1 translocates to endoplasmic reticulum (ER) in response to β‐adrenergic stimulation. To further investigate the function of DRP1 on ER‐lipid droplet (LD) dynamics and the metabolic subsequences, we generated an adipose tissue‐specific DRP1 knockout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 64 publications
(142 reference statements)
1
14
0
Order By: Relevance
“…The dynamin related protein 1 (DRP1), which regulates mitochondria biogenesis and mitophagy, i.e., mitochondrial and peroxisome fission, regulates also endoplasmic reticulum-generated droplets in the adipose tissue, so correlating the correct lipid storage in adipocytes with the mitochondrial survival (Li et al 2020 ). Recent data on lung cancer cell models, reported that DRP1 promotes l -lactate utilization and suppresses oxidative stress from ROS (Hu et al 2020 ).…”
Section: -Lactate Ros and Mitochondria: Role In Skin Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamin related protein 1 (DRP1), which regulates mitochondria biogenesis and mitophagy, i.e., mitochondrial and peroxisome fission, regulates also endoplasmic reticulum-generated droplets in the adipose tissue, so correlating the correct lipid storage in adipocytes with the mitochondrial survival (Li et al 2020 ). Recent data on lung cancer cell models, reported that DRP1 promotes l -lactate utilization and suppresses oxidative stress from ROS (Hu et al 2020 ).…”
Section: -Lactate Ros and Mitochondria: Role In Skin Agingmentioning
confidence: 99%
“…Recent data on lung cancer cell models, reported that DRP1 promotes l -lactate utilization and suppresses oxidative stress from ROS (Hu et al 2020 ). Targeting DRP1 allows to reducing the expression of heart shock proteins (hsp90) and increasing the ROS-mediated cleavage of hsp90, a mechanism that in turn will inhibit the MAPK and PI3K-mediated pathways, the ability of cell to use l -lactate and subsequently the ROS-mediated cell death (li et al 2020 ).…”
Section: -Lactate Ros and Mitochondria: Role In Skin Agingmentioning
confidence: 99%
“…The bands were quantified by using an Odyssey Infrared Imaging system (LI-COR Biosciences). The Cyp3a and CYP3A4 protein levels in C57BL/6J and hCYP3A-MAC/hPXR mice, respectively, were normalized to the KDEL protein level as described in a previous report (50).…”
Section: Sds Page and Western Blottingmentioning
confidence: 99%
“…[20] Of note, noncanonical functions of Drp1 have been postulated for the maintenance of mitochondrial respiration in adult rat cardiomyocytes, and in lipid droplet dynamics in mice adipose tissue. [21,22] The mammalian Drp1 locus is complex and codes for multiple Drp1 isoforms. The human Drp1 locus contains three different alternative splicing sites giving rise to nine different isoforms whose specific functions are mainly unknown.…”
Section: Drp1 a Dynamin That Modulates Organelles Structurementioning
confidence: 99%
“…[ 20 ] Of note, noncanonical functions of Drp1 have been postulated for the maintenance of mitochondrial respiration in adult rat cardiomyocytes, and in lipid droplet dynamics in mice adipose tissue. [ 21,22 ]…”
Section: Introductionmentioning
confidence: 99%